From text to hypertext : decentering the subject in fiction, film, the visual arts, and electronic media - Gaggi, Silvio (Penn studies in contemporary American fiction., 1997)
It is a tenet of postmodern writing that the subject - the self - is unstable, fragmented, and decentered. One useful way to examine this principle is to look at how the subject has been treated in various media in the pre-modern, modern, and postmodern eras. Silvio Gaggi pursues this strategy in From Text to Hypertext, analyzing the issues of subject construction and deconstruction in selected examples of visual art, literature, film, and electronic media. In considering electronic media, Gaggi focuses on computer-controlled media, specifically examples of hypertextual fiction by Michael Joyce and Stuart Moulthrop. Besides recognizing how the computer has enabled artists to create works of fiction in which readers themselves become decentered, Gaggi also observes the impact of literature created on computer networks, where even the limitations of CD-ROM are lifted and the notion of individual authorship may for all practical purposes be lost.